Plumbagin Alleviates Intracerebroventricular-Quinolinic Acid Induced Depression-like Behavior and Memory Deficits in Wistar Rats - Mandeep Kumar Arora; Anish Ratra; Syed Mohammed Basheeruddin Asdaq; Ali A. Alshamrani; Abdulkhaliq J. Alsalman; Mehnaz Kamal; Ritu Tomar; Jagannath Sahoo; Jangra Ashok; Mohd Imran (Molecules, 2022)
Plumbagin, a hydroxy-1,4-naphthoquinone, confers neuroprotection via antioxidant and anti-inflammatory properties. The present study aimed to assess the effect of plumbagin on behavioral and memory deficits induced by intrahippocampal administration of Quinolinic acid (QA) in male Wistar rats and reveal the associated mechanisms. QA (300 nM/4 μL in Normal saline) was administered i.c.v. in the hippocampus. QA administration caused depression-like behavior (forced swim test and tail suspension tests), anxiety-like behavior (open field test and elevated plus maze), and elevated anhedonia behavior (sucrose preference test). Furthermore, oxidative–nitrosative stress (increased nitrite content and lipid peroxidation with reduction of GSH), inflammation (increased IL-1β), cholinergic dysfunction, and mitochondrial complex (I, II, and IV) dysfunction were observed in the hippocampus region of QA-treated rats as compared to normal controls. Plumbagin (10 and 20 mg/kg; p.o.) treatment for 21 days significantly ameliorated behavioral and memory deficits in QA-administered rats. Moreover, plumbagin treatment restored the GSH level and reduced the MDA and nitrite level in the hippocampus. Furthermore, QA-induced cholinergic dysfunction and mitochondrial impairment were found to be ameliorated by plumbagin treatment. In conclusion, our results suggested that plumbagin offers a neuroprotective potential that could serve as a promising pharmacological approach to mitigate neurobehavioral changes associated with neurodegeneration.